PENERAPAN APLIKASI PENCARIAN LOKASI BENGKEL DI KOTA BANDAR LAMPUNG ( STUDI KASUS VESPA) - M Rizky Apriawan; Irwan Adi Pribadi; Yohana Tri Utami (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Applications are ready-made programs that can be used to run commands from application users in order to get more accurate results. The search application for the location of the vespa workshop in the city of Bandar Lampung is made to make it easier for users to find workshops. Information on the location of workshops that have been running so far but is less efficient. In finding the location of the Vespa workshop in the city of Bandar Lampung, still using the manual this method takes a long time to find a Vespa workshop in the city of Bandar Lampung. This research uses simple hill climbing method. This research produces what is in accordance with user needs. The search application for the location of the vespa workshop in Bandar Lampung can see the location of the vespa workshop in the city of Bandar Lampung and can search for the address of the vespa workshop with the location of the nearest vespa workshop from the user quickly and easily.